A new class of seismic damage and performance indices for arch dams via ETA method. (1st March 2016) - Hariri-Ardebili, M.A.; Furgani, L.; Meghella, M.; Saouma, V.E.
Highlights: The ETA and the capacity functions are derived for concrete dams. Over twenty single-variable damage and performance indices are applied to arch dams. Limit state functions for arch dams are identified based on progressive failure methodology. Results of the ETA cross validated by nonlinear transient analyses. Work undertaken by academic researchers (Colorado) and practitioners (Milan/Italy) of academic and practical relevance. Abstract: Quantifying the progressive failure of concrete dams under seismic excitation is essential to risk assessment. This paper addresses this timely topic through Endurance Time Analysis (ETA) methodology coupled with the concepts of Damage Index (DI) and Performance Index (PI). This newly proposed framework is computationally effective in determining engineering demand parameters in dam-reservoir-foundation system. This is achieved through the selection of over twenty single-variable DI and PI based on displacement, joint movement, crack ratio and dissipated energy. ETA and capacity functions are derived, and results are quantitatively compared.